2020
DOI: 10.3171/2019.7.spine19480
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient anterior cervical discectomy and fusion in the ambulatory surgery center setting: safety assessment for the Medicare population

Abstract: OBJECTIVESeveral studies have demonstrated that anterior cervical discectomy and fusion (ACDF) surgery in the outpatient versus hospital setting provides improved efficiency, cost-effectiveness, and patient satisfaction without a compromise in safety or outcome. Recent anecdotal reports, however, have questioned whether outpatient ACDF surgery is safe in the > 65-year-old Medicare population. To date, no clinical study has assessed the safety of outpatient ACDF in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(43 citation statements)
references
References 3 publications
0
43
0
Order By: Relevance
“…6 Large studies previously published by our group have convincingly demonstrated the safety of ambulatory ACDF given careful patient selection, meticulous surgical technique, and standardized perioperative protocols for postoperative observation and complication management. [4][5][6] While the safety of ambulatory ACDF is well established, the cost-effectiveness of ACDF in the ambulatory versus inpatient setting remains unexamined. Most cost-effectiveness studies in the literature compare ACDF to other cervical procedures (e.g.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…6 Large studies previously published by our group have convincingly demonstrated the safety of ambulatory ACDF given careful patient selection, meticulous surgical technique, and standardized perioperative protocols for postoperative observation and complication management. [4][5][6] While the safety of ambulatory ACDF is well established, the cost-effectiveness of ACDF in the ambulatory versus inpatient setting remains unexamined. Most cost-effectiveness studies in the literature compare ACDF to other cervical procedures (e.g.…”
Section: Discussionmentioning
confidence: 92%
“…As detailed in prior reports, this single ASC has rigorous criteria for patient selection, postoperative monitoring, and complication management. [4][5][6] Results may not be generalizable to ASCs lacking these protocols. In addition, this study excluded ASA IV or V patients and those who underwent three-level or four-level ACDF.…”
Section: Discussionmentioning
confidence: 99%
“…Patients could not have myelopathy, had to have surgery with the use of a structural allograft, had to have an operative time under 2 hours, had to have a small neck, and had to have an appropriate discharge environment 33 . Others have since modified these selection criteria; however, a lack of consensus remains 6,[34][35][36] . Based on this series, our results suggest that outpatient surgery should target younger patients who are nonsmokers without anxiety, COPD, hypertension, gastroesophageal reflux, chronic kidney disease, a cerebrovascular accident history, or asthma and have an ASA score of <3.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study are consistent with those reported in the literature. Several studies have shown equal or decreased complication rates in various ambulatory cervical spine procedures, including anterior cervical discectomy and fusion 10,18,29 and posterior cervical decompression. 8,30 However, it is worth noting that the aforementioned studies are not without limitations.…”
Section: Discussionmentioning
confidence: 99%